1996
DOI: 10.1073/pnas.93.20.11063
|View full text |Cite
|
Sign up to set email alerts
|

Identification of peptides specific for cerebrospinal fluid antibodies in multiple sclerosis by using phage libraries.

Abstract: The study of the origin and pathogenetic relevance of the oligoclonal antibodies present in the cerebrospinal fluid (CSF) of multiple sclerosis (MS) patients has been hampered by a lack of specific ligands. We recently reported a general strategy, based on phage-displayed random peptide libraries, to identify ligands for disease-specific antibodies even in the absence of any information on the nature of the pathologic antigen. With this procedure, we identified several peptides specifically recognized by antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 28 publications
0
38
1
Order By: Relevance
“…Identifying the antigenic specificities of MS oligoclonal IgG has been problematic, and the use of random peptide screening as a tool for antigen identification in MS is not novel. Panning of libraries with MS CSF in these earlier studies enriched several peptide sequences (7,8). However, none of the selected peptides reacted universally and specifically with MS CSF and reactivity was also found in serum from a subset of MS patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the antigenic specificities of MS oligoclonal IgG has been problematic, and the use of random peptide screening as a tool for antigen identification in MS is not novel. Panning of libraries with MS CSF in these earlier studies enriched several peptide sequences (7,8). However, none of the selected peptides reacted universally and specifically with MS CSF and reactivity was also found in serum from a subset of MS patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches involving phage display and expression libraries were used to dissect the IgG antibody specificity in the CSF (22)(23)(24)(25). These studies identified possible target peptides in single patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, phage display could provide a means of discerning traces of an earlier etiologic agent that could have initiated an ongoing autoimmune disease. Disease-associated motifs have been sought by phage display in various autoimmune diseases, multiple sclerosis, 41 rheumatoid arthritis, 42 diabetes mellitus, 43 and idiopathic thrombocytopenic purpura. 44 However, these studies have used smaller numbers of patients, or pooled IgG, and although disease-associated motifs have been discerned, in no instance so far has the motif identified a response to a cryptic agent.…”
Section: Figmentioning
confidence: 99%